Oscillation and Stability of Delay Models in Biology - Agarwal, Ravi P.; O'Regan, Donal; Saker, Samir H. (Springer International Publishing : Imprint: Springer, 2014)
Environmental variation plays an important role in many biological and ecological dynamical systems. This monograph focuses on the study of oscillation and the stability of delay models occurring in biology. The book presents recent research results on the qualitative behavior of mathematical models under different physical and environmental conditions, covering dynamics including the distribution and consumption of food. Researchers in the fields of mathematical modeling, mathematical biology, and population dynamics will be particularly interested in this material.